Becquerelite mineral phase: crystal structure and thermodynamic and mechanical stability by using periodic DFT. Issue 43 (10th July 2018) - Colmenero, Francisco; Fernández, Ana María; Timón, Vicente; Cobos, Joaquin
Abstract : The full crystal structure of becquerelite mineral phase was successfully determined using theoretical solid-state methods for the first time. Additionally, a complete study of its thermodynamic and mechanical properties and stability is reported. Abstract : The structure, thermodynamic and mechanical properties of becquerelite mineral, Ca(UO2 )6 O4 (OH)6 ·8H2 O, were studied by means of theoretical solid-state calculations based on density functional theory using plane waves and pseudopotentials. The positions of the hydrogen atoms in the unit cell of becquerelite mineral were optimized theoretically since it was not possible to determine them from X-ray diffraction data by structure refinement. The structural results, including the lattice parameters, bond lengths and X-ray powder pattern, were found to be in excellent agreement with their experimental counterparts. The fundamental thermodynamic properties of becquerelite mineral, including specific heat, entropy, enthalpy and Gibbs free energy, were then computed by performing phonon calculations at the computed optimized structure. Since the experimental values of these properties are unknown, their values were predicted. The values obtained for the isobaric specific heat and entropy of becquerelite at the temperature of 298.15 K were 148.4 and 172.3 J K −1 mol −1, respectively. The computed thermodynamic properties were combined with those of the corresponding elements in order to obtain the enthalpy and Gibbs free energy of formation as a function of temperature. The availability of these thermodynamic properties of formation allowed to determine the enthalpies and free energies and associated reaction constants of a series of reactions involving becquerelite and other uranyl containing materials. Futhermore, knowledge of these properties permitted the study of the thermodynamic stability of becquerelite with respect to a rich set of secondary phases of spent nuclear fuel, including dehydrated schoepite, schoepite, metaschoepite, studtite, metastudtite, rutherfordine and soddyite under different conditions of temperature. Becquerelite is shown to be highly stable in the presence of hydrogen peroxide. It is the second most stable phase under intermediate hydrogen peroxide concentrations (after schoepite), and the fourth most stable phase under high hydrogen peroxide concentrations (after studtite, schoepite and metaschoepite). Finally, the equation of state and elastic properties of this mineral, unknown to date, were determined. The crystal structure of becquerelite was found to be stable mechanically and dynamically. Becquerelite can be described as a brittle material exhibiting large anisotropy and large compressibility in the direction perpendicular to the sheets characterizing the structure of this layered uranyl containing material. The dependence of the elastic properties of becquerelite with respect to the strain orientation is shown to be analogous to that of schoepite mineral. The calculated bulk modulus is also very similar to that of schoepite, B ∼ 31 GPa.